Efficacy and safety of peroxisome proliferator-activated receptor agonists for the treatment of primary biliary cholangitis: a meta-analysis of randomized controlled trials - Tang, Gang; Zhang, Jie; Zhang, Linyu; Xia, Lingying; Tang, Xiaojuan; Chen, Rui; Zhou, Rongxing (Frontiers in Pharmacology, 2024)
Background: Peroxisome proliferator-activated receptor (PPAR) agonists are recognised as a promising treatment for primary biliary cholangitis (PBC). However, the effects and safety of these agonists on PBC remain unexplored. Our study aimed to investigate the efficacy and safety of PPAR agonists in treating PBC.We searched Cochrane Library, and Web of Science, PubMed, and Embase databases from inception to March 15, 2024 for randomised controlled studies (RCTs) that enrolled individuals with PBC treated with PPAR agonists compared with placebo. The primary outcomes were biochemical response and normalization of the alkaline phosphatase (ALP) level.Results: Eight RCTs involving 869 participants in total were included. The meta-analysis revealed that compared to placebo, PPAR agonists increased the rate of biochemical response (RR: 5.53; 95%